2022
DOI: 10.1002/emp2.12740
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone‐associated pulmonary edema in a 3‐year‐old with opioid overdose

Abstract: Background Annually, close to 5000 children under age 6 years are treated in emergency departments or admitted for care due to opioid exposures. Naloxone is effectively used to treat opioid overdose in both children and adults. Non‐cardiogenic pulmonary edema is a rare but serious adverse effect of naloxone administration that has been reported in adults. Case Report We present the case of a 3‐year‐old male with suspected opioid overdose who developed acute hypoxia due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…5,7 Consequently, for acute-on-chronic opioid intoxication, the goal is to use an appropriate amount of naloxone-just enough naloxone to prevent aspiration or apnea-while avoiding an excess that might lead to withdrawal symptoms. 8,9 The maximum permissible dose of naloxone that can be given remains uncertain. Numerous textbooks and articles mention a cumulative limit of 10 mg in total.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Consequently, for acute-on-chronic opioid intoxication, the goal is to use an appropriate amount of naloxone-just enough naloxone to prevent aspiration or apnea-while avoiding an excess that might lead to withdrawal symptoms. 8,9 The maximum permissible dose of naloxone that can be given remains uncertain. Numerous textbooks and articles mention a cumulative limit of 10 mg in total.…”
Section: Discussionmentioning
confidence: 99%
“…In the world of adult emergency medicine, the side effect of naloxoneinduced noncardiogenic pulmonary edema is a well-known risk that providers fear upon opiate or opioid reversal. However, in the pediatric age group, there have only been a few cases reported, indicating that they may be at lower risk [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Linking noncardiac pulmonary edema to naloxone in opioid overdose may be dubious [116], since opioid overdose itself may also be associated with the condition. Nevertheless, recent reports have connected naloxone to pulmonary edema [129][130][131]. Moreover, Farkas et al reported that naloxone doses exceeding 4.4 mg increased the risk for pulmonary complications after opioid overdose [132].…”
Section: Adverse Effectsmentioning
confidence: 99%